Numerical analysis of parallel jet-in-crossflow - Lim, Avion (2019)
The parallel twin jet-in-crossflow (PJICF) configuration is a variant of the heavily-studied single jet-in-crossflow (SJICF) configuration. A lack of computational studies on the near-field dynamics of the PJICF prompted this study. Insights on the trajectory and counter-rotating vortex pairs were derived from a steady Reynolds-Averaged Navier Stokes computational model of the PJICF. The jet trajectories had discrepancies with that of empirical studies, with only trajectories at low velocity ratios providing good convergence with experiments. Asymmetry in the jet trajectories was observed to decrease with increasing separation distance and decreasing velocity ratios. The trajectory scaling equation by Pratt and Baines’ for SJICF configuration showed good correlation with the PJICF configuration. The counter-rotating vortex pairs produced also provided good insight into the near-field dynamics and coincided well with empirical studies, with the inner vortices from each jet cancelling each other out very early on in the flow at smaller separation distances. An exploration of the symmetry boundary condition along the symmetry plane of the PJICF configuration also yielded good agreement compared with full mesh results in both trajectory and counter-rotating vortex pairs; the only deviations being found in highly asymmetric cases with low separation distance and high velocity ratio.